2014
DOI: 10.1007/s10877-014-9590-6
|View full text |Cite
|
Sign up to set email alerts
|

Automation of anaesthesia: a review on multivariable control

Abstract: Anaesthesia is a multivariable problem where a combination of drugs are used to induce desired hypnotic, analgesia and immobility states. The automation of anaesthesia may improve the safety and cost-effectiveness of anaesthesia. However, the realization of a safe and reliable multivariable closed-loop control of anaesthesia is yet to be achieved due to a manifold of challenges. In this paper, several significant challenges in automation of anaesthesia are discussed, namely model uncertainty, controlled variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 102 publications
(99 reference statements)
0
10
0
Order By: Relevance
“…More concretely, the administration of the hypnotic is made automatically, but the administration of the analgesic is manually made by a clinician. A detailed introduction to anesthesia as a control problem together with a good overview of the state of the art can be found in Lemos et al [15] and Chang et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…More concretely, the administration of the hypnotic is made automatically, but the administration of the analgesic is manually made by a clinician. A detailed introduction to anesthesia as a control problem together with a good overview of the state of the art can be found in Lemos et al [15] and Chang et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…1) SISO Model: The pharmacokinetic/pharmacodynamic (PK/PD) model is a compartmental model that illustrates both the drug distribution in the human body and its effect on certain physiological systems. For anesthesia, the pharmacokinetics are represented by a linear compartmental model that defines the concentration of the administered drug in different parts of human body, while the pharmacodynamics are represented by a static nonlinear function (i.e., Hill curve) relating the resulting drug concentration to the measured effect (e.g., BIS index) [174], [190].…”
Section: B Modelingmentioning
confidence: 99%
“…Concurrently, other research groups developed closed-loop systems for propofol using a variety of mathematical algorithms for robotic drug delivery. 21 In 2001, Struys et al 22 demonstrated that induction and maintenance of hypnosis using a patient individualized model-based adaptive closedloop control system for propofol is feasible. In their randomized trial, 10 patients received automated administration of propofol setting the target BIS value at 50.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%